2017
DOI: 10.1002/btm2.10050
|View full text |Cite
|
Sign up to set email alerts
|

ICAM‐1‐targeted nanocarriers attenuate endothelial release of soluble ICAM‐1, an inflammatory regulator

Abstract: Targeting of drug nanocarriers (NCs) to intercellular adhesion molecule‐1 (ICAM‐1), an endothelial‐surface protein overexpressed in many pathologies, has shown promise for therapeutic delivery into and across this lining. However, due to the role of ICAM‐1 in inflammation, the effects of targeting this receptor need investigation. Since ICAM‐1 binding by natural ligands (leukocyte integrins) results in release of the “soluble ICAM‐1” ectodomain (sICAM‐1), an inflammatory regulator, we investigated the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
(128 reference statements)
1
20
0
Order By: Relevance
“…Given that inflammation develops and contributes significantly to the progression and response to treatment of LDs [1,4], this would represent a secondary benefit of using this targeting strategy. As an example, our recent study using anti-ICAM NCs indicated that since ICAM-1 is endocytosed bound to anti-ICAM NCs, this temporarily removes ICAM-1 from the endothelial surface and, in turn, reduces the levels of soluble ICAM-1 released by endothelial cells [45]. Soluble ICAM-1 has been shown to be generated upon cleavage of membrane-expressed ICAM-1 and is a pro-inflammatory mediator [46].…”
Section: Discussionmentioning
confidence: 99%
“…Given that inflammation develops and contributes significantly to the progression and response to treatment of LDs [1,4], this would represent a secondary benefit of using this targeting strategy. As an example, our recent study using anti-ICAM NCs indicated that since ICAM-1 is endocytosed bound to anti-ICAM NCs, this temporarily removes ICAM-1 from the endothelial surface and, in turn, reduces the levels of soluble ICAM-1 released by endothelial cells [45]. Soluble ICAM-1 has been shown to be generated upon cleavage of membrane-expressed ICAM-1 and is a pro-inflammatory mediator [46].…”
Section: Discussionmentioning
confidence: 99%
“…Also, by providing such an enhancement in the delivery to multiple tissues and across endothelial barriers, this strategy may help reduce the dose and, perhaps, frequency of administration, altogether lowering side effects. To this extent, a thorough investigation is warranted in order to advance this strategy, yet preliminary results show that mice tolerate these injections well and lack gross effects, including histological appearance, lack of edema or decrease in the endothelial permeability, and actually reduction of endothelial release of soluble ICAM-1, a factor involved in inflammation [448]. …”
Section: Additional Approaches Toward the Optimization Of Lysosomamentioning
confidence: 99%
“…In terms of scientific topics, BioTM has focused on subjects where Engineering, Chemical Engineering in particular, has made a strong fundamental and translational impact on the field. These topics include drug delivery, Nucleic acid delivery, Regenerative Medicine, Biotechnology, Nanomedicine, Biomedical Devices, and immunotherapy . We look forward to continue building our strengths in these fields and expand the list to include additional key areas.…”
mentioning
confidence: 99%